„In der englischen Sprache zu schreiben war eigentlich eine Zumutung für mich“ - Dirk Weissmann (Recherches Germaniques)
George Tabori (1914-2007), playwriter, stage director and Georg Büchner Prize recipient in 1992, is considered to be one of the most emblematic figures of German theater from the 1980s and 1990s. Brought up in a bilingual Jewish family of Budapest, Tabori wrote however almost exclusively his work in English and therefore achieved his first breakthrough in America. Contrary to other protagonists of the German intercultural literature, Tabori, who fled the Nazi terror, didn’t (re)find his way back in German language even though he moved in the Federal Republic of Germany in the beginning of the 1970s. This paper aims to analyze the unusual linguistic position of this important author from the German theatre’s recent history. For this purpose, we propose to contextualise Tabori’s career among other comparable cases of multilingualism in the 20th century German literature. Elias Canetti (1905-1994) and Klaus Mann (1906-1949), two renowned writers whose literary works and biographies are also shaped by prolonged exiles in the English-speaking world as well as translingual writing, will serve in this respect as points of comparison.